Hadoop on data analytics - Gee, Denny Jee King. (2012)
Twitter is a micro-blogging application that entails strong capabilities to share and convey ideas effectively through social connectivity. The data sets generated by Twitter could easily breakthrough millions of tweets per day. It could be computational infeasible to perform information mining from a massive amount of data. Hence, we took an approach in adopting the MapReduce Framework provided by Apache Hadoop.